Becoming a Clinical Teacher: Identity Formation in Context. (October 2019) - Cantillon, Peter; Dornan, Tim; De Grave, Willem
Abstract : Purpose: Most clinical teachers have not been trained to teach, and faculty development for clinical teachers is undermined by poor attendance, inadequate knowledge transfer, and unsustainability. A crucial question for faculty developers to consider is how clinicians become teachers "on the job." Such knowledge is important in the design of future workplace-based faculty development initiatives. The authors conducted a scoping review of research on the relationship between becoming a clinical teacher and the clinical environments in which those teachers work. Method: In June 2017, using the scoping review design described by Levac et al (2010), the authors searched 12 databases. They subjected the articles discovered to four phases of screening, using iteratively developed inclusion/exclusion criteria. They charted data from the final selection of articles and used thematic analysis to synthesize findings. Results: Thirty-four research reports met the inclusion criteria. Most (n = 24) took an individualist stance toward identity, focusing on how teachers individually construct their teacher identity in tension with their clinician identities. Only 10 studies conceptualized clinical teacher identity formation as a social relational phenomenon, negotiated within hierarchical social structures. Twenty-nine of the included studies made little or no use of explicit theoretical frameworks, which limited their rigor and transferability. Conclusions: Clinicians reconciled their identities as teachers with their identities as clinicians by juggling the two, finding mutuality between them, or forging merged identities that minimized tensions between educational and clinical roles. They did so in hierarchical social settings where patient care and research were prioritized above teaching. Abstract : Supplemental Digital Content is available in the text.